2017
DOI: 10.15809/irriga.2017v22n1p204-219
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento E Produção De Girassol Ornamental Irrigado Com Diferentes Lâminas E Diluições De Água Residuária

Abstract: Crescimento e Produção de girassol ornamental irrigado com diferentes lâminas E diluições de água residuária  MARIANA LAYS ANDRADE OLIVEIRA¹; VITAL PEDRO DA SILVA PAZ²; KAROLINE SANTOS GONÇALVES³ E GREICE XIMENA SANTOS OLIVEIRA4 ¹Núcleo de Engenharia de Água e Solo, Universidade Federal do Recôncavo da Bahia, UFRB, Cruz das Almas, BA, mary_lays@hotmail.com²Programa de Pós-Graduação em Engenharia Agrícola, Universidade Federal do Recôncavo da Bahia, UFRB, Cruz das Almas, BA, vitalpaz@ufrb.edu.br³Programa de Pós… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 0 publications
5
12
0
4
Order By: Relevance
“…Regarding GSI, it was observed that there was a difference between the treatments (Table 2), were the substrate T2 and T4 were that obtained the highest values, and the lowest result was found in T3, with reduction of 0.57 GSI (24.2%). According to Oliveira et al (2009) seeds with high GSI values are more resistant to the adverse conditions of the medium, as they germinate faster and decrease the initial stage of development of seedling production, thus it is expected in the present study, that the substrates with higher GSI (T2 and T4) have said characteristics. This is probably because these two treatments (T2 and T4) are composed of coconut fiber, since according to Carrijo et al (2002), this material is essential when used as a substrate in the germination of ornamental seeds, because it presents high durability, and physical properties such as density and total porosity essential in the production of seedlings.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Regarding GSI, it was observed that there was a difference between the treatments (Table 2), were the substrate T2 and T4 were that obtained the highest values, and the lowest result was found in T3, with reduction of 0.57 GSI (24.2%). According to Oliveira et al (2009) seeds with high GSI values are more resistant to the adverse conditions of the medium, as they germinate faster and decrease the initial stage of development of seedling production, thus it is expected in the present study, that the substrates with higher GSI (T2 and T4) have said characteristics. This is probably because these two treatments (T2 and T4) are composed of coconut fiber, since according to Carrijo et al (2002), this material is essential when used as a substrate in the germination of ornamental seeds, because it presents high durability, and physical properties such as density and total porosity essential in the production of seedlings.…”
Section: Resultsmentioning
confidence: 72%
“…Due to its high profitability, demand for small areas, intensive production and the rapid return of invested capital, ornamental sunflower production has aroused great interest among producers and investors (OLIVEIRA et al, 2017). According to Curti et al (2012), ornamental sunflower is mainly marketed as a cut flower, where this sector represents 34% of the flower and ornamental plants production chain in Brazil (JUNQUEIRA and PEETZ, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Results obtained in the present study corroborate those reported by Oliveira et al (2017), who observed no significant effect of the treatments on plant height in any period of evaluation in conventional cultivation (in pots) of ornamental sunflower, cv. Anão de Jardim, using different water depths and wastewater dilutions along with mineral fertilization [14].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, Oliveira et al (2017) observed at 35 days after transplanting for the same cultivar irrigated with water containing 75% of wastewater showed on average two leaves more than the plants irrigated with supply water under organic fertilization. In the final evaluation, these authors observed no significant difference in the NL under different treatments, which had on average 30.05 leaves [14].…”
Section: CV (%)mentioning
confidence: 87%
“…In this sense, Rawashdeh (2017), verified the maximization of seed yield and oil production in sunflower plants irrigated with treated domestic wastewater. Oliveira et al (2017) studied the effects of five dilutions of treated domestic wastewater in supply water on the development and production of sunflower. They reported that irrigation with wastewater caused no significant change on external diameter of flower bud, beginning of flowering and the full opening of head and irrigation, while the wastewater favored the development of sunflower, especially in the dilution of 100% domestic wastewater.…”
Section: Introductionmentioning
confidence: 99%